Temporal dynamics within a contemporary latitudinal diversity gradient - Jonathan A. D. Fisher; Kenneth T. Frank; Brian Petrie; William C. Leggett; Nancy L. Shackell (Ecology Letters, 2008)
Poleward declines in species diversity [latitudinal diversity gradients (LDG)] remain among the oldest and most widespread of macroecological patterns. However, their contemporary dynamics remain largely unexplored even though changing ecological conditions, including global change, may modify LDG and their respective ecosystems. Here, we examine temporal variation within a temperate Northwest Atlantic LDG using 31 years of annual fisheries‐independent surveys and explore its dynamics in relation to a dominant climate signal [the wintertime North Atlantic Oscillation (NAO)] that varies interannually and alters the latitudinal gradient of Northwest Atlantic continental shelf bottom water temperatures. We found that the slopes of the annual LDG vary dramatically due to changes in geographic distributions of 100+ species, variations that are concealed within the cumulative, static LDG. These changes are strongly associated with changes in NAO sign and strength. This is the first illustration of temporal dynamics in a contemporary LDG and the first demonstration of the speed at which local environmental variations can alter an LDG. Our findings underscore the need to investigate factors that modify LDG separately from those that contribute to their origins.